Results of therapeutic keratoplasty using porcine keratoxenoimplant in severe destructive inflammations of the human cornea (Ukrainian Journal of Ophthalmology, 2026)
Introduction. One of key methods of surgical treatment for patients with severe destructive inflammatory process (SDIP) of the cornea is keratoplasty. Being performed as an urgent intervention in SDIP of the cornea, keratoplasty is the only method to preserve the eye as an organ and, in some cases, to create prospects for optic surgery. The problem of donor material shortage is of a special relevance since the legal base providing donor material harvesting is incomplete and as a result of increased military, traffic and home traumatism. The acute shortage of donor material for keratoplasty (KP) forces searching new graft materials. One of such material is a porcine cornea which has many similarities with a human cornea in regard to its structure and biomechanical parameters.Material and Methods. We retrospectively analyzed the outcomes of 32 patients with severe destructive corneal inflammatory diseases of various etiologies, who underwent therapeutic keratoplasty using cryolyophilized keratoxenoimplant of the porcine cornea at Corneal Pathology Department of the Filatov Institute from January 2013 to December 2015.Results. As a result of treatment, the eye as an organ was preserved. Not transparent keratoxenoimplant survival was observed in late postoperative period. Of 37 patients, undergone lamellar or penetrating keratoplasty, keratoxenoimplant survival was semitransparent in 9 cases (33.3%) and opaque in 18 cases (66.7%). Biological dressing survived opaque in two cases; and in three cases it resolved within 2-8 weeks after operation. At late follow-up period after keratoxenotransplantation partial lysis of xenograft was noted in 7 eyes (21.9%); of them, repeat keratoplasty using donor human cornea was performed in 5 cases, single-stage glaucoma surgery was in one case, and single-stage cataract extraction in another one. In the late follow-up, glaucoma surgery was performed in 5 eyes (15.6%). As a result of xenotransplantation, visual acuity improved in 5 eyes (15.6%), did not change in 24 eyes (75%), and changed for the worse in 3 eyes (9.6%). In destructive processes of small diameter with paracentral and peripheral location, we could preserve and improve visual functions. Prospects for optic surgery performance were kept in 20 patients (62.5%).Conclusion. Thus, under the urgent condition when donor human cornea is not available, keratoxenoimplant can be used for therapeutic keratoplasty in order to manage the inflammatory process and to preserve the eye.
Keywords: destructive inflammatory corneal disease; therapeutic keratoplasty; keratoxenoimplant